Multilocus phylogeny of Gryllus field crickets (Orthoptera: Gryllidae: Gryllinae) utilizing anchored hybrid enrichment - Gray, David A.; Weissman, David B.; Cole, Jeffrey A.; Lemmon, Emily Moriarty; Lemmon, Alan R. (Zootaxa, 2020)
We present the first comprehensive molecular phylogeny of Gryllus field cricket species found in the United States and Canada, select additional named Gryllus species found in Mexico and the Bahamas, plus the European field cricket G. campestris Linnaeus and the Afro-Eurasian cricket G. bimaculatus De Geer. Acheta, Teleogryllus, and Nigrogryllus were used as outgroups. Anchored hybrid enrichment was used to generate 492,531 base pairs of DNA sequence from 563 loci. RAxML analysis of concatenated sequence data and Astral analysis of gene trees gave broadly congruent results, especially for older branches and overall tree structure. The North American Gryllus are monophyletic with respect to the two Old World taxa; certain sub-groups show rapid recent divergence. This is the first Anchored Hybrid Enrichment study of an insect group done for closely related species within a single genus, and the results illustrate the challenges of reconstructing the evolutionary history of young rapidly diverged taxa when both incomplete lineage sorting and probable hybridization are at play. Because Gryllus field crickets have been used extensively as a model system in evolutionary ecology, behavior, neuro-physiology, speciation, and life-history and life-cycle evolution, these results will help inform, interpret, and guide future research in these areas.